2018
DOI: 10.1097/bot.0000000000001297
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Orthopaedic Volunteers and Their Local Hosts in Low- and Middle-Income Countries: Are We on the Same Page?

Abstract: Objective: Our goal was to compare the perceptions of overseas orthopaedic volunteers and their hosts in low-and middle-income countries (LMICs) regarding the role of international volunteerism. We also sought to determine if differences in perception exist between trainee and fully trained orthoapedic surgeon volunteers. Methods: Surveys with similar multiple-choice and open-ended questions were administered to 163 Health Volunteers Overseas orthopaedic volunteers (response rate 45%) and 53 members of the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…Despite strong interest in these rotations from orthopaedic programs 2,3,8 , literature reporting their motivations and impact is sparse. Thus, for this analysis, we included surgical resident rotations beyond orthopaedics to identify practices that minimize harm and share benefits with LMIC partners 43,44 . The available data from the LMIC perspective shows that the most important component of HIC collaboration is sustained investment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite strong interest in these rotations from orthopaedic programs 2,3,8 , literature reporting their motivations and impact is sparse. Thus, for this analysis, we included surgical resident rotations beyond orthopaedics to identify practices that minimize harm and share benefits with LMIC partners 43,44 . The available data from the LMIC perspective shows that the most important component of HIC collaboration is sustained investment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite strong interest in these rotations from orthopaedic programs 2 , 3 , 8 , literature reporting their motivations and impact is sparse. Thus, for this analysis, we included surgical resident rotations beyond orthopaedics to identify practices that minimize harm and share benefits with LMIC partners 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a survey of orthopedic volunteers and host country staff indicated "Although volunteers and hosts typically believed that the volunteers were strongly motivated by the altruistic aspects of volunteering, host responses suggested that they perceived that volunteers were also motivated by their desire to practice and learn new techniques and enhance their professional careers." 30 The authors postulated that "Discrepancies in perceptions of volunteer motivations could be due to a paternalistic attitude of the volunteers, who may have preconceived notions that they come from a superior medical system and that their primary role was to teach rather than participate in a bidirectional relationship". 30 In an accompanying editorial to the previously mentioned general surgery survey, it was stated that "there must be competent supervision provided for all trainees so that unsuspecting and uninformed patients are not harmed by inadequately trained residents.…”
Section: Surgical Education Pitfallsmentioning
confidence: 99%
“…30 The authors postulated that "Discrepancies in perceptions of volunteer motivations could be due to a paternalistic attitude of the volunteers, who may have preconceived notions that they come from a superior medical system and that their primary role was to teach rather than participate in a bidirectional relationship". 30 In an accompanying editorial to the previously mentioned general surgery survey, it was stated that "there must be competent supervision provided for all trainees so that unsuspecting and uninformed patients are not harmed by inadequately trained residents. 31 Meanwhile, how many hospitals in the United States do we see LMIC medical students, residents, and fellows walking around going to operating rooms and trying to operate?…”
Section: Surgical Education Pitfallsmentioning
confidence: 99%